FULLERENE C60 STRENGTHEN TOLUENE TOXIC EFFECT ON ENZYMES SYSTEM STATE OF XENOBIOTICS BIOTRANSFORMATION - Palytsia, L.M.; Korda, M.M.; Mudra, A.E.; Fedoniuk, L.Y. (World of Medicine and Biology, 2019)
Nanoparticles, due to the wide-scale use in many countries in different areas of production, life and medicine, assume the character of a new global anthropogenic factor, which can be characterized by a potential danger to public health. Preliminary toxicology studies have shown that nanoparticles are characterized by ability to penetrate through biological membranes and physiological barriers of the body and serve as “agents” in the body of heavy metals, pesticides, compounds of halogens, etc. So the question arises about the need for fundamental understanding of toxicological properties of nanoparticles when they penetrate into the body with “classic” chemical toxicants.The aim of this research is to investigate the effect of fullerenes (C60) combination with known chemical toxicant toluene on the activity of the first and second group enzymes of xenobiotics metabolism phase in rat’s liver. Laboratory rats received intraperitoneal injections of fullerene suspension (60 mg/kg), toluene (0.5 ml/kg) or toluene with dissolved fullerenes. UDP-glucuronosyltransferase, ethoxyresorufin-O-deethylase (EROD), glutathione-S-transferase activity were identified in microsomes liver in as a time series starting in hour 3 of the experiment and up to hour 72.Mathematical processing of received data was made in the Department of Statistical Research of I. Horbachevsky Ternopil State Medical University using statistical applications Microsoft Excel 2007 and STATISTICA v6. The results show the average ± SEM from 8 experiments. Got values were compared with the usage of Mann-Witney non-parametric criterion. The changes were considered statistically reliable with р
Keywords: fullerenes; toluene; enzymes of xenobiotics biotransformation